On a method for constructing one-frequency solutions of a nonlinear wave equation - Sokil, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
A method for constructing one-frequency solutions of nonlinear wave equations is suggested. This approach is based on a modified representation of asymptotic expansions by using special periodic Atebfunctions. This method makes it possible to obtain approximate solution of the problem under consideration without difficulty.